Fruit-derived Polyphenol supplementation improves exercise performance: a meta-analysis of 29 randomised controlled trials - Zamri, F. N. S.; Linoby, A.; Norhamazi, I.; Mursyid, S.; Naimah, M.; Haslan, A. N.; Noor, M. A. M. (Journal of Physical Education and Sport, 2022)
Fruit-derived polyphenols (FDP) are rich in antioxidants and have anti-inflammatory properties. They have also been shown to improve exercise performance. FDP supplementation may increase muscle oxygenation during exercise through the nitric oxide (NO) pathway by increasing both NO bioavailability and endothelial NO synthase expression. The current meta-analysis systematically evaluates the relevant randomised controlled trials to verify whether FDP supplementation improves exercise performance compared to the placebo (PLA). Relevant studies have been examined using five electronic databases: PubMed, EMBASE, Ovid [MEDLINE], SPORTDiscus and Web of Science. Other relevant articles from grey literature sources were also manually examined. Fifty-five trials from 29 studies met the inclusion criteria, involving a total of 651 subjects. The overall effect size yielded an average standardised mean difference (SMD) of 0.29 (95% CI: 0.21 to 0.38, p<0.001), indicating that FDP supplementation provides a small yet significant performance benefit over PLA. In the subgroup analysis, the current study found that the highest effect size is from the co-ingestion of multiple sources of FDP (SMD = 0.40 [95% CI: 0.13 to 0.65], p<0.001), followed by cherries and berries, then pomegranates (SMD = 0.28 [95% CI: 0.18 to 0.37], p<0.001 and SMD = 0.23 [95% CI: 0.02 to 0.43], p=0.03, respectively). These findings suggest that the ergogenic effects of dietary polyphenol supplementation naturally sourced from fruit does improve exercise performance and can potentially benefit athletes in the context of supplementation strategy.